Initial and Final Setting Time Determination of 3D Printing Mortar with Kenaf Powder Addition - Ismail, Amira; Ibrahim, Mustaffa (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The construction industry is likely to undergo significant alterations from conventional method to the potentially disruptive technologies such as 3D concrete printing (3DCP). The use of the natural fibers in the mortar for 3DCP applications will increase the environmental awareness, allowing for further research for new sustainable materials in construction industry. The contribution of this study to identify the effects of kenaf powder as a natural fiber on setting time.as a first stage for determination on the fresh properties of the 3D printing mortar. The goals of this research is to create a good mix design that passes the experimental works and be able to be used on 3DCP.This experimental works is an important parameter to guarantee that mixes harden at appropriate time to ensure the bonding between each layer of the 3D printing mortar. Ordinary Portland cement (OPC), dust sand, organic plasticizer and polymer were used as a part of 3D printing mortar. Vicat apparatus in accordance to ASTM standard is used as an apparatus to determine the initial and final setting time. In general, the addition of the kenaf powder with 30%, 40% and 50% effect the both initial and final setting time. Kenaf powder with 40% weight by cement and 325g water content was chosen as an acceptable mixture to be applied on 3DCP because it required the appropriate time for harden enough to stack layer by layer without changing its forms and passed the standard setting time of 600 minutes.